Pengaruh Kepemimpinan Instruksional dan Keadilan Prosedural Terhadap Citizenship Behavior (CB): Studi Kausal Terhadap Guru SMK Negeri di Kabuaten Lebak - Aufa Maftuhah; I Made Putrawan; Suryadi Suryadi (Program Studi Manajemen Pendidikan, 2018)
This study aims to determine the effect of instructional leadership and procedural justice on citizenship behavior. The study was conducted at Lebak vocational high school by using a survey method with path analysis applied in testing hypothesis and 118 samples selected by simple random sampling. The finding of the research are. (1) Instructional leadership has a direct positive effect on procedural justice. (2) Procedural justice has a direct positive effect on citizenship behavior. (3) Instructional leadership has a direct positive effect on citizenship behavior, (4) Instructional leadership has a indirect effect on citizenship behavior through procedural justice. Based on the findings in this study, it could be concluded that the influence of the instructional leadership and procedural justice are the important factors to influence teacher citizenship behavior.